Assessment of Seven Clinical Tumor Markers in Diagnosis of Non-Small-Cell Lung Cancer - Chen, Zhong-qing; Huang, Ling-sha; Zhu, Bo (Disease Markers, 2018)
Background. The correlation between tumor markers (TM) and TNM stage of non-small-cell lung cancer (NSCLC) has not been widely reported. Methods. TM levels (CEA, CA125, CA15-3, CA19-9, CA72-4, CYFRA21-1, and SCC-Ag) in 424 cases of lung adenocarcinoma (LAC), 166 cases of lung squamous cell carcinoma (LSCC), and 103 cases of benign chest disease (BCD) were analyzed before treatment. Results. By Kendall’s tau-b correlation analysis, CEA, CA125, CA15-3, CA19-9, CA72-4, CYFRA21-1, and SCC-Ag were correlated with T stage of LAC (r=0.235, p<0.05; r=0.298, p<0.05; r=0.254, p<0.05; r=0.063, p<0.05; r=0.080, p<0.05; r=0.268, p<0.05; and r=0.080, p<0.05). CEA, CA125, CA15-3, CA19-9, CA72-4, and CYFRA21-1 were correlated with N stage of LAC (r=0.356, p<0.05; r=0.415, p<0.05; r=0.340, p<0.05; r=0.117, p<0.05; r=0.175, p<0.05; and r=0.351, p<0.05). CEA, CA125, CA15-3, CA19-9, CA72-4, and CYFRA21-1 were correlated with M stage of LAC (r=0.365, p<0.05; r=0.353, p<0.05; r=0.293, p<0.05; r=0.135, p<0.05; r=0.169, p<0.05; and r=0.312, p<0.05). CA125, CYFRA21-1, and SCC-Ag were correlated with T stage of LSCC (r=0.202, p<0.05; r=0.233, p<0.05; and r=0.099, p<0.05). CA125 and CYFRA21-1 were correlated with N stage of LSCC (r=0.178, p<0.05 and r=0.284, p<0.05). CA125, CA15-3, and CYFRA21-1 were correlated with M stage of LSCC (r=0.214, p<0.05; r=0.152, p<0.05; and r=0.213, p<0.05). Combining hazard ratio, AUC, sensitivity, specificity, NPV, and PPV, it was concluded that CEA and CYFRA21-1were the most related TM of LAC. SCC-Ag and CYFRA21-1 were the most related TM of LSCC. Conclusions. CEA combined with CYFRA21-1 contributed to auxiliary diagnosis of LAC. CYFRA21-1 combined with SCC-Ag contributed to auxiliary diagnosis of LSCC. CEA, CA125, CA15-3, CA19-9, CA72-4, and CYFRA21-1 were correlated with primary tissue and metastasis of LAC. CA125 and CYFRA21-1 were correlated with primary tissue and metastasis of LSCC.